(untitled) (Research, Society and Development, 2020)
This essay aims to analyze the debate on microemancipation widespread in Critical Management Studies, confronting the objectives of critical theory with regard to emancipation. Methodologically, we sought to observe the guidelines of Meneghetti (2011) and Bertero (2011) that present reflections on the production of essays in the field of organizational studies. The concept of emancipation for critical theory is taken up again from authors of the Frankfurt School. The concept of microemancipation is discussed from the work of Alvesson and Willmott (2010). Later on, the debate among Brazilian intellectuals about the concept of microemancipation and its adherence to the purpose of emancipation present in critical theory is analyzed. Finally, it is argued that the acceptance of the concept of microemancipation does not imply the negation of the ideal of emancipation advocated by critical theory, even if the concept is, in some cases, used in a way that is detrimental to the emancipatory purpose of criticism.